2018
DOI: 10.1071/sh18059
|View full text |Cite
|
Sign up to set email alerts
|

Cost and anonymity as factors for the effective implementation of pre-exposure prophylaxis: an observational study among gay, bisexual and other men who have sex with men in Singapore

Abstract: Background HIV pre-exposure prophylaxis (PrEP) is currently offered by several public and private clinics at unsubsidised prices in Singapore, but to date, no information is available on the effect of these services. This study sought to assess the knowledge and uptake of, and willingness to use PrEP among gay, bisexual and other men who have sex with men (GBMSM) in Singapore. Methods: Recruitment was conducted through Grindr®, a geosocial networking application for GBMSM. Results were quantitatively analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…First, this study found that accessing PrEP at the anonymous testing site (compared with government-run hospitals and clinics) and follow-up care visits at nongovernment hospital settings with a longer follow-up time of once a year (compared with quarterly visits) were valued by potential users and could encourage PrEP use, as would lower prices. These findings corroborate findings from prior studies in Singapore, 14,15 which suggest that anonymity of sexual health services and costrelated issues were the main barriers to accessing PrEP among GBMSM. Second, this study also found that utility for PrEP use decreased with increasing perceived risk of HIV and other STI acquisition per sexual act while using PrEP for participants in general, however this inverse relationship exhibited a steeper curve for perceived risk of HIV acquisition compared with that of perceived STI acquisition risk, likely due to greater perceptions of HIV severity and susceptibility in GBMSM.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…First, this study found that accessing PrEP at the anonymous testing site (compared with government-run hospitals and clinics) and follow-up care visits at nongovernment hospital settings with a longer follow-up time of once a year (compared with quarterly visits) were valued by potential users and could encourage PrEP use, as would lower prices. These findings corroborate findings from prior studies in Singapore, 14,15 which suggest that anonymity of sexual health services and costrelated issues were the main barriers to accessing PrEP among GBMSM. Second, this study also found that utility for PrEP use decreased with increasing perceived risk of HIV and other STI acquisition per sexual act while using PrEP for participants in general, however this inverse relationship exhibited a steeper curve for perceived risk of HIV acquisition compared with that of perceived STI acquisition risk, likely due to greater perceptions of HIV severity and susceptibility in GBMSM.…”
Section: Discussionsupporting
confidence: 90%
“…This study follows a qualitative study on the acceptability of PrEP and a cross-sectional study on PrEP use among GBMSM in Singapore. 14,15 This study was conducted as a web-based survey hosted on Sawtooth Software (Sawtooth Software, Inc, Provo, UT), and disseminated by Grindr. Grindr is a popular application (app) for smartphones and tablets that was designed to allow GBMSM to connect with other individuals through the geolocation capabilities of individual devices.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tan et al describe some other PrEP implementation challenges from the experience in Singapore, 25 where PrEP is available at unsubsidised prices. Tan et al argue that even in high-income settings, national financing schemes will be important to ensure large-scale access to PrEP.…”
mentioning
confidence: 99%